Evaluation of Human Basic Movement Systems Based on Artificial Intelligence - Fayzullaev Bekhzod Bakhtiyorovich; Anarkulova Rano Oybek qizi; Jovliev Abbasjon Mirmukhsin ogli (Zien Journals, 2022)
One of the fastest growing areas today is artificial intelligence. This article gives a brief overview of the assessment of human locomotor systems based on artificial intelligence. Today, information technology is developing rapidly in our lives.
Keywords: Artificial Intelligence; Deep Blue; IBM Computer